1976
DOI: 10.1002/jobm.19760160602
|View full text |Cite
|
Sign up to set email alerts
|

Production physiology and properties of a novel fungal fibrinolytic enzyme

Abstract: A potent extracellular fibrinolytic enzyme was obtained from cultures of the imperfect fungus Fusarium semitectum under certain growth conditions. Nitrate addition to cultures increased enzyme production. The enzyme showed a versatile proteolytic activity against several protein substrates including casein, gelatin, haemoglobin, bovine serum albumin, and fibrin from both buffalo and human sources.Optimal fibrinolysis occurred at p H values around 7.0. The fibrinolytic activity exhibited marked heat stability i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…This is probably due to the limited diffusion of the tested substances into the gel material. The adverse effect of high phosphate concentrations on productivity of the fibrinolytic enzyme by immobilized P. chrysogenum H9 is in accordance with results obtained by Fayek et al (1976) who found that at high phosphate concentrations (0.25 M), the production of fibrinolytic enzyme by Fusarium semitectum was inhibited.…”
Section: Discussionsupporting
confidence: 80%
“…This is probably due to the limited diffusion of the tested substances into the gel material. The adverse effect of high phosphate concentrations on productivity of the fibrinolytic enzyme by immobilized P. chrysogenum H9 is in accordance with results obtained by Fayek et al (1976) who found that at high phosphate concentrations (0.25 M), the production of fibrinolytic enzyme by Fusarium semitectum was inhibited.…”
Section: Discussionsupporting
confidence: 80%
“…Some stimulate the activity of the fibrinolytic blood systems. These include streptokinase, obtained from Streptococcus haemolytlcum, and tricholysin, from the fungus Trichothecium roseum, while those with fibrinolytic action, but unknown as activators of fibrinolysis in the body of the animal enzyme, were isolated mainly from species of the genus Aspergillus [4].…”
Section: Introductionmentioning
confidence: 99%
“…Fungi synthesize proteases in a more diverse way than bacteria. Unlike bacterial proteases, fungal proteases have a low reaction rate and are less tolerant to high temperatures; however, they are active at pH (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) and exhibit a wide substrate specificity [13]. It has been established that basidial macromycetes (Basidiomycota division) are able to synthesize serine, thiol, aspartyl metalloproteinases, which are also found in fungi of other systematic groups in different proportions.…”
Section: Introductionmentioning
confidence: 99%